Application Of Hutagogy System For Transforming Basic Proficient Course Training At Pusdiklatcab Jombang - Fauziah, Anik Ida; Widodo, J. Priyanto (Gudang Jurnal Multidisiplin Ilmu, 2024)
This study aims to analyze the application of the Hutagogy (Self-Determined Learning) system in basic proficient course training at Pusdiklatcab Jombang, East Java. Hutagogy is a learning approach that gives trainees greater control and responsibility in organizing and directing their own learning. The research method used is qualitative research with a case study approach. Data were collected through participatory observation, interviews with trainees and instructors, and analysis of training-related documents. The results of this study are expected to provide insight into the effectiveness and benefits of implementing the Hutagogy system in the context of basic proficient course training. A significant 75% strongly agree with the use of diverse media in learning, indicating an understanding of the value of multimedia technologies. Furthermore, 50% strongly agree that students actively participate in course assessments, demonstrating a willingness to evaluate and improve the learning process. Finally, an overwhelming 81.3% support a thorough approach to assessment that includes pre-tests, post-tests, reviews, feedback, and reflections, demonstrating commitment to a holistic evaluation process. And all of the finding explained that hutagogy was applied at Pusdiklatcab Jombang , East Java.